2018
DOI: 10.33607/bjshs.v1i96.73
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Women`s Body Dissatisfaction, Sense of Coherence and Physical Activity

Abstract: Background. Socio-cultural pressure exerted by the environment and the media makes the majority of women take care of their bodies. That is especially true in Western culture which promotes slimmer women in recent decades.Methods. Two questionnaires were used in this research: Body Shape Questionnaire and Sense of Coherence scale. Research participants were 79 women aged 34.6 ± 3.76 years. Results. After six months of regular fitness classes women’s satisfaction of their body and their sense coherence level  i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Bearing in mind the whole body of evidence for the positive relationship between SOC and all abovementioned indicators of mental and physical well-being, we hypothesised that SOC could also be positively correlated with the BS, both in the study and in control groups. In addition, we expected that this positive correlation would be stronger in the treated group, which could be interpreted in accordance with Antonovsky's concept of generalised resistance resources, 16,28 where SOC is of high importance for health stability in the face of severe stress. To our best knowledge, this study is the first analysis of these correlations in a group of breast cancer survivors.…”
Section: Manageability Manifests Itself In An Individual's Belief Abosupporting
confidence: 66%
See 3 more Smart Citations
“…Bearing in mind the whole body of evidence for the positive relationship between SOC and all abovementioned indicators of mental and physical well-being, we hypothesised that SOC could also be positively correlated with the BS, both in the study and in control groups. In addition, we expected that this positive correlation would be stronger in the treated group, which could be interpreted in accordance with Antonovsky's concept of generalised resistance resources, 16,28 where SOC is of high importance for health stability in the face of severe stress. To our best knowledge, this study is the first analysis of these correlations in a group of breast cancer survivors.…”
Section: Manageability Manifests Itself In An Individual's Belief Abosupporting
confidence: 66%
“…12 Dumciene et al (2015) found the strongest correlations between the general SOC as well as manageability alone and body shape dissatisfaction in healthy women. 28 The Buddeberg-Fischer group investigated associations between body image, SOC, and well-being among more than 500 students. They found strong correlations between the SOC, well-being, body image, and concerns about eating behaviour and BS.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Social appearance anxiety is a concept that has been recently investigated by researchers in association with participation in sports (Berry & Howe, 2004;Brunet & Sabiston, 2009;Dumciene, Gedviliene, & Mickevicius, 2015;Eriksson, Baigi, Marklund, & Lindgren, 2008;Haase, Prapavessis, & Owens, 2002). Studies conducted in exercise psychology have clearly highlighted the positive effects of regular participation in physical activity on physical and psychological health (Aşçı, 2002;Dishman & Jackson, 2000;Fox, 1997;Paluska & Schwenk, 2000).…”
Section: Introductionmentioning
confidence: 99%